2015
DOI: 10.1103/physreva.91.062501
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten spectroscopy in the EUV range observed at a high-temperature superconducting electron-beam ion trap

Abstract: We have recorded extreme ultraviolet spectra from W 11+ to W 15+ ions using a flat-field spectrometer installed at the Shanghai high-temperature superconducting electron-beam ion trap. The spectra were recorded at beam energies ranging between 200 and 400 eV and showed spectral lines and transition arrays in the 170-260Å region. The charge states and spectra transitions were identified by comparison with calculations using a detailed relativistic configuration interaction method and collisional-radiative model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
8
31
1
Order By: Relevance
“…Experimental investigations are hampered by the fact that plasmas, including plasma in electron-beam ion traps (EBITs) [19][20][21][22][23][24], that are typically required to produce ions in intermediate charge states, contain a mixture of ions of different charge states with overlapping spectral features. Charge-state-resolved spectra can be obtained using suitable subtractions of spectra acquired under various plasma conditions [25][26][27][28] or by employing genetic algorithms [29].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental investigations are hampered by the fact that plasmas, including plasma in electron-beam ion traps (EBITs) [19][20][21][22][23][24], that are typically required to produce ions in intermediate charge states, contain a mixture of ions of different charge states with overlapping spectral features. Charge-state-resolved spectra can be obtained using suitable subtractions of spectra acquired under various plasma conditions [25][26][27][28] or by employing genetic algorithms [29].…”
Section: Introductionmentioning
confidence: 99%
“…For higher charge states, e.g. W 13+ , several observation using an EBIT have been reported [10,11,12] for the EUV region although the identification is still in controversy. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Some of those computations, however, indicated that according to the computed level structure, the 5p levels would not be particularly highly populated either directly or via cascades except possibly in much more highly charged ions along the isoelectronic sequence [28,29]. To my knowledge, no one doubts that the Berlin group may well have observed EUV lines belonging to the Pm-like spectrum of tungsten, except for a recent paper from Shanghai [30]; the author list of this new paper includes one of the Berlin paper authors who so far had insisted that all was well. However, the Vilkas computations [28] have long since indicated that the prominent decays of the 5p levels proposed decades before would not materialize in reality.…”
Section: Complex Spectramentioning
confidence: 99%